Ultrasonic characteristics and severity assessment of lung ultrasound in COVID-19 pneumonia in wuhan, china: A retrospective, observational study (2020)
The clinical application of lung ultrasound (LUS) in the assessment of coronavirus disease 2019 (COVID-19) pneumonia severity remains limited. Herein, we investigated the role of LUS imaging in COVID-19 pneumonia patients and the relationship between LUS findings and disease severity. This was a retrospective, observational study at Tongji Hospital in Wuhan, on 48 recruited patients with COVID-19 pneumonia, including 32 non-critically ill patients and 16 critically ill patients. LUS was performed and the respiratory rate oxygenation (ROX) index, disease severity, and confusion, urea nitrogen, respiratory rate, blood pressure and age (CURB-65) score were recorded on days 0–7, 8–14, and 15–21 after symptom onset. Lung images were divided into 12 regions, and the LUS score (0–36 points) was calculated. Chest computed tomography (CT) scores (0–20 points) were also recorded on days 0–7. Correlations between the LUS score, ROX index, and CURB-65 scores were examined. LUS detected COVID-19 pneumonia in 38 patients. LUS signs included B line (34/38, 89.5%), consolidation (6/38, 15.8%), and pleural effusion (2/41, 5.3%). Most cases showed more than one lesion (32/38, 84.2%) and involved both lungs (28/38, 73.7%). Compared with non-critically ill patients, the LUS scores of critically ill patients were higher (12 (10–18) vs 2 (0–5), p < 0.001). The LUS score showed significant negative correlations with the ROX index on days 0–7 (r = –0.85, p < 0.001), days 8–14 (r = –0.71, p < 0.001), and days 15–21 (r = –0.76, p < 0.001) after symptom onset. However, the LUS score was positively correlated with the CT score (r = 0.82, p < 0.001). The number of patients with LUS-detected lesions decreased from 27 cases (81.8%) to 20 cases (46.5%), and the LUS scores significantly decreased from 4 (2–10) to 0 (0–5) (p < 0.001) from days 0–7 to 17–21. We conclude that LUS can detect lung lesions in COVID-19 pneumonia patients in a portable, real-time, and safe manner. Thus, LUS is helpful in assessing COVID-19 pneumonia severity in critically ill patients.